The Temporal and Spatial Characteristics and Influencing Factors of Low-Carbon Economy Efficiency and Science and Technology Development Level in China’s Provinces From the Perspective of Uncoordinated Coupling - Guangming, Yang; Qingqing, Gui; Fengtai, Zhang; Guofang, Gong; Yunrui, Yang (Frontiers in Environmental Science, 2022)
In order to achieve sustainable development, low-carbon economic efficiency (LCEE) is particularly important in China. Therefore, this study uses SBM-DEA model to evaluate the LCEE of 30 provinces in China from 2008 to 2017. Based on the uncoordinated coupling model, this study discusses the interaction between China’s provincial LCEE and scientific and technological development level (STDL), and uses the panel VAR model to consider the interactive response relationship between China’s provincial LCEE and STDL. The research shows that the uncoordinated coupling degree (UCCD) between the STDL and LCEE in 30 provinces showed a decreasing trend as a whole during the research period. In terms of spatial distribution, the provinces with UCCD less than 0.5 mainly concentrated in the eastern and southern provinces, gradually spread to the north, and showed positive spatial autocorrelation, with significant spatial accumulation effect. From the perspective of influencing factors, patents, urbanization level, traffic level and financial development have significant positive effects on promoting the coordinated development of STDL and LCEE. From the relationship between them, the STDL has a positive promoting effect on LCEE, but the mechanism of the two is not obvious enough. Therefore, it is necessary to emphasize the coordinated development of low-carbon economy and science and technology, and promote the development of low-carbon economy through scientific innovation.